In Search of Magnetic Properties of Samarium Cobalt (Sm2Co17) within a Low-Temperature Sintering Process - Poppy Puspitasari; A. Muhammad; A. A. Permanasari; T. Pasang; S. M. S. N. S. Zahari; N. A. Ahmad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Samarium cobalt is known as super high density magnetic material with large magnetic anisotropy energy. Samarium–cobalt exhibits manipulative magnetic properties as a rare-earth material which has different properties in a low sintering temperature. It is therefore of paramount importance to investigate samarium cobalt (Sm2Co17) magnetic properties in the low temperature sintering condition. Sm2Co17, which is utilized in this research, is synthesized via the sol–gel process at sintering temperatures of 400, 500, and 600 °C. Subsequently, the crystallites indicate the formation of a single-phase Sm2Co17 on all the samples in all temperature variations. Moreover, the peaks in the X-ray diffraction analysis of crystallite sizes calculated using the Scherrer equation are 17.730, 15.197, and 13.296 nm at 400, 500, and 600 °C. Through scanning electron microscopy, the particles are found to be relatively large and agglomerated, with average sizes of 143.65, 168.78, and 237.26 nm. The functional groups are also analyzed via Fourier-transform infrared spectroscopy, which results in the appearance of several bonds in the samples, for example, alkyl halides, alkanes, and esters with aromatic functional groups on the fingerprint area and alkynes, alkyl halides, and alcohol functional groups at a wavelength of above 1500 cm. The test results of the magnetic properties using vibrating-sample magnetometer (VSM) revealed high coercivity and retentivity in the samples sintered at 400 °C. However, the highest saturation occurs in the samples sintered at 600 ℃. At a low sintering temperature (below 1000 °C), samarium cobalt shows as the soft magnetic material. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).